Para onde vai a periferia? Análise sobre a produção e transformação de áreas periféricas: o caso do bairro Feu Rosa - Serra/ES - Lemes, Vinicius Lima (2020)
This dissertation intends to understand the formation and transformation of peripheral areas, considering the forms of production of urban housing. Our understanding is that the performance of the real estate market, which was already emerging as a form o